Korean Pop dan Pengaruhnya Terhadap Gaya Hidup Siswa SMK Negeri 2 Muaro Jambi - Nita Hermayani (Prodi Bimbingan dan Konseling Islam (BPI) Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2021)
The background of this research is that every part of the world has a different culture. One of the cultures that are favored by young people in Indonesia today is the Hallyu Wave or Korean culture and many people call it K-Pop (Korean Pop) to become a very popular culture. The research used in this research is qualitative research. This research was conducted at the State 2 Muaro Jambi Vocational High School (SMK) located in Suka Makmur Village, Sungai Bahar District, Muaro Jambi Regency. The results found in this study are that the shape of the impact of K-Pop at SMKN 2 Muaro Jambi is that the students at the school collect accessories, albums, and lightsticks from their K-pop idols, and also follow the hairstyle and hair color models. And the form of the impact is a positive impact where the existence of K-pop can add insight to students about foreign cultures, one of which is the State of Korea, besides that it makes students learn about audio visuals because it is in accordance with multimedia majors as well as especially at SMKN 2 Kab Muaro Jambi there was the establishment of aextracurricularcover dance. The negative impact is the reduced interaction of students with parents because they prefer to spend their time watching Korean drama films, so when they talk about their idols there is a sense of connection when they talk about it. Meanwhile, the effort of the teacher's role is to let students like their idols by facilitating students' interest in liking foreign cultures but